Absence of Singularity in Schwarzschild Metric in the Vector Model for Gravitational Field - On, Vo Van (Communications in Physics, 2012)
In this paper, based on the vector model for gravitational field we deduce an equation to determinate the metric of space-time. This equation is similar to equation of Einstein. The metric of space-time outside a static spherically symmetric body is also determined. It gives a small supplementation to the Schwarzschild metric in General theory of relativity but the singularity does not exist. Especially, this model predicts the existence of a new universal body after a black hole.